Using outcome trajectory evaluation to assess HarvestPlus’ contribution to the development of national biofortification breeding programs - Douthwaite, Boru; Johnson, Nancy L.; Wyatt, Amanda (International Food Policy Research Institute, 2022)
While the key role that policy plays in sustainable development has long been recognized, rigorously documenting the influence of research on policy outcomes faces conceptual, empirical and even political challenges. Addressing these challenges is increasingly urgent since improving policies—broadly defined—is at the heart of the structural transformation agenda. This paper describes the use of a new evaluation method—outcomes trajectory evaluation (OTE), based on both evaluation and policy process theory—to explore the influence of HarvestPlus, a large and complex research for development program focused on improving nutrition, on a specific policy outcome, namely the establishment of crop biofortification breeding programs in national agricultural research institutes in Bangladesh, India and Rwanda. The findings support claims of significant HarvestPlus contributions to the establishment of the programs while also raising issues that need to be monitored moving forward to ensure sustainability. The paper also discusses the pros and cons of the OTE approach in terms of both methodological rigor and program learning. In particular, the fact that HarvestPlus is a long-running program allows us to reflect on how a “backward looking” approach such as OTE builds on and complements the more “forward looking,” theory of change-based approaches that informed HarvestPlus programming and evaluation during its earlier, highly-successful phases. Such a long-run perspective is rare in development evaluation and it offers important lessons for how to think about and plan for evaluation over the course of a complex agriculture research for development program.